Pengaruh Penyaluran Zakat Pada Kesejahteraan Mustahik (Studi Kasus BAZNAS Kabupaten Hulu Sungai Selatan) - Manik Mutiara Sadewa; Anisa Agustina (P3M Politeknik Negeri Banjarmasin, 2024)
This study aims to determine the effect of zakat distribution on the welfare of mustahik in BAZNAS Hulu Sungai Selatan Regency. The research method used is quantitative with a descriptive approach. The sampling technique used is saturated sampling with a data collection method through a questionnaire. The respondents used as samples in this study were mustahik in Hulu Sungai Selatan Regency in 2022 as many as 30 people. The results of hypothesis testing partially showed that zakat distribution has an effect on the welfare of mustahik because the t-count value is 5,241> t-table 2,045 and significance (0,000 < 0,05). This study proves that mustahik welfare increases after zakat distribution.